POTENTIAL PRODUCTION OF DEMERSAL FISH STOCK IN THE MALACCA STRAIT OF INDONESIA - Purwanto Purwanto (Indonesian Fisheries Research Journal, 2015)
Malacca Strait is one of the main fishing areas for demersal fishery in Indonesia. To support the management of that fishery, an assessment of the demersal fish stock was conducted. This study estimated that the maximum sustainable yield and the optimal catch per unit effortof demersal fishery in the Malacca Strait were about 106.8 thousand tons/year and 28.5 tons per unit of Danish seine, respectively, resulting from the operation of 3,752 Danish seines. Unfortunately, fishing effort was higher than its optimum level and the fish stock was over-exploited since 2003. To recover the demersal fish stock to its optimum level and to ensure the optimal fish production from demersal fishery in the Malacca Strait, it was necessary to reduce fishing effort at about 67% from its level in 2011.